Penerapan Design Thinking dalam Rancangan Website Penyewaan Lapangan Badminton GOR Anugrah - Joosten, Joosten; Sudarto, Sudarto; Mulia, Rudolf (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
GOR Anugrah is a company that provides badminton court rental services. In the current court rental process at GOR Anugrah, there are still several issues that need to be addressed, with the main problem being the lack of information about court availability. This often causes potential renters to wait for confirmation from the management. In addition, renters also face challenges such as double bookings and complicated payment processes due to inefficient rental management. The author aims to analyze and design a website that simplifies the court rental process. To conduct the analysis and design, the author applies the Design Thinking method, which includes the stages of empathy, define, ideate, prototype, and test. In conclusion, the author hopes that the designed badminton court rental website can serve as a solution for GOR Anugrah. With the implementation of this website, it is expected that potential renters will find it easier to access availability information, make reservations, and complete payments online. Moreover, by enhancing brand awareness through the website, GOR Anugrah is expected to attract more new renters and expand its market reach.